Hydrogel-based delivery system applied in the local anti-osteoporotic bone defects - Gong, Yining; Bu, Yazhong; Li, Yongliang; Hao, Dingjun; He, Baorong; Kong, Lingbo; Huang, Wangli; Gao, Xiangcheng; Zhang, Bo; Qu, Zechao; Wang, Dong; Yan, Liang (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoporosis is an age-related systemic skeletal disease leading to bone mass loss and microarchitectural deterioration. It affects a large number of patients, thereby economically burdening healthcare systems worldwide. The low bioavailability and complications, associated with systemic drug consumption, limit the efficacy of anti-osteoporosis drugs currently available. Thus, a combination of therapies, including local treatment and systemic intervention, may be more beneficial over a singular pharmacological treatment. Hydrogels are attractive materials as fillers for bone injuries with irregular shapes and as carriers for local therapeutic treatments. They exhibit low cytotoxicity, excellent biocompatibility, and biodegradability, and some with excellent mechanical and swelling properties, and a controlled degradation rate. This review reports the advantages of hydrogels for adjuvants loading, including nature-based, synthetic, and composite hydrogels. In addition, we discuss functional adjuvants loaded with hydrogels, primarily focusing on drugs and cells that inhibit osteoclast and promote osteoblast. Selecting appropriate hydrogels and adjuvants is the key to successful treatment. We hope this review serves as a reference for subsequent research and clinical application of hydrogel-based delivery systems in osteoporosis therapy.